Seroprevalence of Q fever among metropolitan and non‐metropolitan blood donors in New South Wales and Queensland, 2014–2015. Issue 7 (8th March 2019) - Gidding, Heather F; Faddy, Helen M; Durrheim, David N; Graves, Stephen R; Nguyen, Chelsea; Hutchinson, Penny; Massey, Peter; Wood, Nicholas
Abstract: Objectives: To estimate the prevalence of exposure to the causative agent of Q fever ( Coxiella burnetii ) and of current infections among blood donors in Australia. Design, setting: Cross‐sectional study in metropolitan Sydney and Brisbane, and in non‐metropolitan regions with high Q fever notification rates (Hunter New England in New South Wales; Toowoomba in Queensland). Participants: Blood donors attending Red Cross collection centres during October 2014 – June 2015 who provided sera and completed a questionnaire on Q fever vaccination status, diagnosis and knowledge, and exposure history. Main outcome measures: Age‐ and sex‐standardised seroprevalence of phase II IgG antibodies to C. burnetii (indicating past exposure) and independent risk factors for seropositivity; presence of C. burnetii DNA (indicating current infection and risk of transmission by blood transfusion). Results: 2740 donors (94.5% response rate) completed the questionnaire and supplied sera for analysis. Crude antibody seroprevalence was 3.6%. Standardised seroprevalence was higher in non‐metropolitan than metropolitan regions (NSW, 3.7% v 2.8%; Queensland, 4.9% v 1.6%; statistically significant only in Queensland). Independent predictors of antibody seropositivity were regular contact with sheep, cattle, or goats (adjusted odds ratio [aOR], 5.3; 95% CI, 2.1–14), abattoir work (aOR, 2.2; 95% CI, 1.2–3.9), and assisting at an animal birth (aOR, 2.1; 95% CI, 1.2–3.6). Having lived in a rural area but having only rare or no contact with sheep, cattle or goats was itself a significant risk factor ( v never lived rurally: aOR, 2.5; 95% CI, 1.1–5.9). 40% of people in groups recommended for vaccination were aware of the vaccine; 10% of people in these groups had been vaccinated. C. burnetii DNA was not detected in 1681 non‐metropolitan samples, suggesting that transmission by blood donation is unlikely. Conclusions: Given their exposure to multiple risk factors, vaccination against Q fever should be considered for all rural residents.